A responsive website designed for intelligent courses planning - Ding, Jin (2019)
Before the start of every semester, the Academic Programmes Officers need to generate a full set of course timetables and teaching staff calendars. Currently, the officers are using a Windows application that can output an individual timeline for each course and a personal schedule for every teaching staff in a Microsoft Word file. However, in the digital age, there is a compelling need to having a copy of the teaching calendar on digital devices including mobile phones, laptops, and even smart watches. Therefore, the project aims to design and implement an application that is compatible with different Operating Systems. The main functionalities include generating online teaching assignment forms, retrieving online assignments, calculating the teaching staff calendars, and sending confirmation emails to the teaching staffs with the digital schedule synchronised to the commonly used calendars such as Outlook Calendar, Google Calendar, and Apple Calendar. In the light of the restrictions and requirements provided by the officers, a full stack MongoDB, React, Node and Express web application is implemented. The report will cover the contributions of the author through the last two semesters. Starting with a brief introduction on the background and scope of the project, the report will then reveal the overall system architecture, project planning details, implementation process, testing procedures and results, and conclusion and future work.